FAQIH: Framework for Agent-Based Query-Enabled Integrated Information for Health and Nutrition - Tijerino, Yuri A.; El-Bassuny, Tarek Helmy; Bradshaw, Jeffrey M. (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2008)
As the processes of urbanization and globalization continue to gain momentum, issues relating to interdependencies among water, food, nutrition and public health policy have increased in complexity and scope. Thus, it is no longer sufficient for subject-matter experts to develop models for each of their underlying domains of expertise (e.g., nutrition, healthcare, and land and water management) independently. Both expert stakeholders and ordinary citizens would benefit from reliable and continually up-to-date models on which to base their decisions. In this preliminary overview paper, the authors propose to develop a Framework for Agent-based Query-Enabled Integrated Information for Health and Nutrition (FAQIH) to support healthcare professionals, policy makers, and citizens to obtain the knowledge they seek.